Serum lipids, tHcy, hs-CRP, MDA and PON-1 levels in SCH and overt hypothyroidism: effect of treatment - Singh, Sarika; Dey Sarkar, Purmina (Acta Biomedica Atenei Parmensis, 2014)
Background. Thyroid hormones are the most important factors involved in the regulation of the basal metabolic condition, as well as in the oxidative metabolism. Hypothyroidism is associated with increased cardiovascular morbidity, which cannot be fully explained by the atherogenic lipid profile observed in these patients. Aim: Study of serum lipids, tHcy, hs-CRP, MDA and PON-1 levels in SCH and overt Hypothyroidism: Before and After Therapy” Methods: 100 hypothyroid (56 SCH and 44 OH) and 100 controls, with a mean age range 20–65 years were enrolled for this study. Serum TSH, FT3 and FT4 levels were evaluated by Chemiluminescence Enzyme Immunoassay. T-CHO by CHOD – POD Method. HDL-C by Direct Detergent Method. TG by GPO-POD Method. LDL-C by Friedewald’s Formula. tHcy by auto analyzers. hs-CRP by Latex–High Sensitivity. MDA by Kei Satoh Method. PON-1 by spectrophotometric method using P-Nitrophenyl Acetate. All tests were done before and after 8-12 week of treatment. Result: Pretreatment, in both SCH and OH groups, we found significantly higher serum TSH (P<0.001), TC, LDL-C, TG (P<0.01, P<0.001 and P<0.05) in SCH and (P<0.001) in OH, hs-CRP (P<0.05 and P<0.001) and MDA levels (P<0.001) than in controls. A significant decrease was seen in FT3 and FT4 (P<0.05 and P<0.001) and PON-1 activity (p<0.01 and p<0.001) in both groups than in controls, whereas HDL levels were lower and Homocysteine levels were found to be higher in only OH groups. L-thyroxine therapy significantly decreased serum TSH, TC, LDL-C, TG and t-Hcy (P<0.001) concentrations in both groups. Conclusion: Our study showed that both SCH and OH patients have elevated atherogenic and oxidative stress markers. Increased CRP and homocysteine might be a key molecule linking inflammation to oxidative stress in atherosclerosis.